First record of Athyreacaridae (Acari: Heterostigmata) from Asia with description of two new species of Athyreacarus from India and Sri Lanka - Khaustov, Alexander A.; Frolov, Andrey V. (Zootaxa, 2020)
Mites of the family Athyreacaridae are recorded from Asia for the first time. Two new species of Athyreacarus are described, A. indicus sp. nov., collected on the beetles Bolbohamatum laevicolle and B. marginale in India, and A. brevisetosus sp. nov., collected on a beetle Bolboceras sp. in Sri Lanka. An updated key to species of the genus Athyreacarus is provided.